Study of the therapeutic effect of oral propranolol combined with topical timolol maleate in the treatment of mixed maxillofacial hemangioma in infants - LI Jiapeng; CHEN Jufeng; ZHANG Guorun; XIAN Dan; LI Jin; WANG Lei; ZHANG Guoyi (口腔疾病防治, 2019)
Objective To observe the treatment effect of oral propranolol combined with topical timolol maleate for infantile maxillofacial mixed hemangioma and provide evidence for clinical treatment. Methods Ninety-seven cases of infantile maxillofacial mixed hemangioma were enrolled. The cases were randomly divided into A and B groups: 50 cases in group A were treated with oral propranolol combined with topical timolol maleate, and 47 cases in group B were treated with oral propranolol only. The changes in the color, volume, and texture of the tumors were recorded before and after treatment, and color ultrasonography of the lesion area was performed. The follow-up time was 1-12 months. The differences in the curative effect, effective time and adverse reaction between the two groups were compared. Results The effective rate of group A was 92.0% (46/50) and that of group B was 74.5% (35/47), with a statistical significance (P < 0.05). The mean time of treatment in group A was 4.2 months and that in group B was 5.5 months. Compared with group B, the treatment time of group B was shorter (t=3.211, P < 0.05), and no serious adverse reactions occurred in both groups. Conclusion Oral propranolol combined with topical timolol maleate is effective in the treatment of mixed hemangioma of the maxillofacial region in infants.